Ex vivo biomechanical evaluation of a bone-screw-fastener for tibial plateau leveling osteotomy - Kettleman, William S.; Jaffe, Michael H.; Wills, Robert W.; Dietz, Sara J.; Elder, Steve H. (Frontiers in Veterinary Science, 2023)
The objective of this study was to investigate the effect of a bone-screw-fastener (BSF) on stiffness and failure characteristics of a tibial plateau leveling osteotomy (TPLO) construct under cyclic loading conditions. The authors hypothesized that BSF would result in superior biomechanical stability compared with locking buttress screws (LBS). Twelve pairs of canine cadaveric pelvic limbs were included in this ex vivo biomechanical study. A TPLO was performed using a 3.5mm locking TPLO plate and stabilized using either LBS or BSF. Cyclic loading was performed for 30,000 cycles at 4Hz with a peak-load of 1000N (50N valley). The cyclic test was then continued by stepwise incremental increase of peak-load at a rate of 75N per 500 cycles until failure. Cycles to failure for LBS (44,260 +/- 5,770) and BSF (41,540 +/- 7,686) were not significantly different (P = 0.36). Maximum force for LBS (3,134 +/- 797N) and BSF (2,940 +/- 831N) was not significantly different either (P = 0.58). Dynamic stiffness for LBS (1,778 +/- 932 N/mm) and BSF (1,574 +/- 677 N/mm) was not significantly different (P = 0.58). Stabilization of the TPLO with BSF provided no advantage to biomechanical stability under cyclic axial loading conditions when compared to the LBS. BSF may be an acceptable alternative to traditional locking screws for TPLO; however, further research is warranted prior to clinical application.